Mythical origins of the actin cytoskeleton. (February 2021) - Akıl, Caner; Kitaoku, Yoshihito; Tran, Linh T.; Liebl, David; Choe, Han; Muengsaen, Duangkamon; Suginta, Wipa; Schulte, Albert; Robinson, Robert C.
Abstract: The origin of the eukaryotic cell is one of the greatest mysteries in modern biology. Eukaryotic-wide specific biological processes arose in the lost ancestors of eukaryotes. These distinctive features, such as the actin cytoskeleton, define what it is to be a eukaryote. Recent sequencing, characterization, and isolation of Asgard archaea have opened an intriguing window into the pre-eukaryotic cell. Firstly, sequencing of anaerobic sediments identified a group of uncultured organisms, Asgard archaea, which contain genes with homology to eukaryotic signature genes. Secondly, characterization of the products of these genes at the protein level demonstrated that Asgard archaea have related biological processes to eukaryotes. Finally, the isolation of an Asgard archaeon has produced a model organism in which the morphological consequences of the eukaryotic-like processes can be studied. Here, we consider the consequences for the Asgard actin cytoskeleton and for the evolution of a regulated actin system in the archaea-to-eukaryotic transition.